Determinants of Entrepreneurial Intention Among Students: Perceived Role of the Academic and Socio-Institutional Environment - Gbaguidi, Léandre; Amidjogbé, S. T. Ignace; Abodohoui, Alexis (Journal of Comparative International Management)

(untitled) (Management Futures, 2023)
This article aims to analyze the influence of the academic and socio-institutional environment on the entrepreneurial intention of students in Benin. Using the snowball sampling technique, data collection was carried out based on a questionnaire distributed to a sample of 325 students from public and private universities in Benin. The estimation of the ordered logistic regression model with STATA 13 shows that the entrepreneurial intention of students in Benin is characterized by entrepreneurial education, innovation, and risk propensity. Moreover, unlike government support, variables related to perceived cultural norms and social legitimacy of entrepreneurship negatively moderate the effect of entrepreneurship education on students’ entrepreneurial intention in Benin. As a contribution to the literature, this paper shows the crucial role of students’ education in the acquisition of entrepreneurial skills that enhance entrepreneurial capacity and lead them to develop skills that help them start businesses.